2015
DOI: 10.2147/ijn.s87190
|View full text |Cite
|
Sign up to set email alerts
|

Free radical scavenging in vitro and biological activity of diphenyl diselenide-loaded nanocapsules: DPDS-NCS antioxidant and toxicological effects

Abstract: Selenium compounds, such as diphenyl diselenide (DPDS), have been shown to exhibit biological activity, including antioxidant effects. However, the use of DPDS in pharmacology is limited due to in vivo pro-oxidative effects. In addition, studies have shown that DPDS-loaded nanocapsules (DPDS-NCS) have greater bioavailability than free DPDS in mice. Accordingly, the aim of this study was to investigate the antioxidant properties of DPDS-NCS in vitro and biological activity in mice. Our in vitro results suggeste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(39 reference statements)
0
4
0
Order By: Relevance
“…In this study, inhibition of δ-ALA-D, an increase in aspartate (AST) and alanine aminotransferase (ALT) activities, and a decrease in urea levels were observed, with no effect on creatinine levels, showing that the compound had a hepatotoxic effect but no effect on renal function [56]. A very important finding is that in studies using diselenides-loaded nanocapsules, no toxic effects on mice were shown, which gives hope for a reduction in their harmful properties and possible application in human trials in the future [55,58]. Summarizing the toxicological data of diselenides in in vivo studies, more information from further animal studies on them is needed to unambiguously determine the exact mechanism of their harmful effects on the body, as well as methods to prevent them.…”
Section: Diselenidesmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, inhibition of δ-ALA-D, an increase in aspartate (AST) and alanine aminotransferase (ALT) activities, and a decrease in urea levels were observed, with no effect on creatinine levels, showing that the compound had a hepatotoxic effect but no effect on renal function [56]. A very important finding is that in studies using diselenides-loaded nanocapsules, no toxic effects on mice were shown, which gives hope for a reduction in their harmful properties and possible application in human trials in the future [55,58]. Summarizing the toxicological data of diselenides in in vivo studies, more information from further animal studies on them is needed to unambiguously determine the exact mechanism of their harmful effects on the body, as well as methods to prevent them.…”
Section: Diselenidesmentioning
confidence: 99%
“…Oral administration of 30 mg/kg (supranutritional dose of diphenyl diselenide) for 8 months was non-toxic in rabbits, whereas acute intraperitoneal administration of 1.56 and 15.6 mg/kg was hepatotoxic to them, while a dose of 156 mg/kg was lethal to 85% of the population [52]. The main mechanism responsible for the toxic properties of diselenides is their prooxidant activity, which involves interaction with functionally relevant -SH (thiol) groups of proteins, leading to their oxidation and loss/decrease in their function [53,55,56]. Depletion of intracellular GSH is one of these effects [53,55].…”
Section: Diselenidesmentioning
confidence: 99%
See 2 more Smart Citations